Effects of Using Microorganisms in Soil Improvement, Sayyaboury Province - SYHA, Phonepaseuth; NORBOUASAMAI, Fongsamouth; PHOUTHAXAY, Phonesavanh; THAMMAVONG, Khamko; VILAYSAK, Bounsuang (Souphanouvong University Journal Multidisciplinary Research and Development, 2023)
This experiment is the use of beneficial microorganisms in soil improvement in Xayabuli province, the objective to study the effect of using beneficial microorganisms (Bacillus subtilis) from 0 - 16 ml in soil improvement by fermenting in a jar and leaving it in an outdoor condition similar to the real field conditions. Fermented soil is an organic mixture (soil:cow manure:rice straw ratio 90:8:2) with different microorganism rates (0, 4 ml, 8 ml, 12 ml and 16 ml). And the experiment was Using the Randomized Completely Block Design (RCBD) experimental model, it includes 4 replicates and 5 experiments. From the data collection and analysis was showed the result of microbial load has resulted in soil chemical composition (pH, OM, N, P2O5 and K2O) changes respectively, but the experiment found that: using the amount of microorganisms from 4 - 8 ml, there is no statistical difference, the difference will be seen when using the amount of microorganisms 12 ml or more. The results of the experiment showed that the experiments using the amount of 12 and 16 ml of microorganisms caused the soil chemical composition to change a lot with a statistical difference at the 95% confidence level, the most positive change in soil chemical composition is the use of 16 ml of microorganisms. And compared with control 0 ml was 2 time